Canagliflozin alters the gut, oral, and ocular surface microbiota of patients with type 2 diabetes mellitus - Wang, Limin; Liang, Chenghong; Song, Xiaojian; Jia, Xiaoyan; Wang, Xiudan; Zhang, Yun; Xie, Qinyuan; Zheng, Nan; Yuan, Huijuan (Frontiers in Endocrinology, 2023)
Background:Modifications in the gut microbiota may be a crucial factor in the efficacy of canagliflozin(Cana) in managing patients with type 2 diabetes mellitus(T2DM). However, the interplay between oral and ocular surface microbiota and this treatment remains poorly explored. Aim This study aimed to assess alterations in the gut, oral, and ocular surface microbiota pre-and post-Cana treatment in patients with T2DM. Methods:In this 30-day, controlled before-and-after study, 21 treatment-naïve patients with T2DM received sole treatment with Cana (100 mg/day), and were matched with 10 healthy controls based on gender and age. Using 16S rRNA sequencing, changes in the gut, oral, and ocular surface microbiota pre-and post-Cana treatment were assessed and compared with those of healthy controls. Concurrently, diabetes-related clinical parameters were recorded over the study period. The trial was registered in the Chinese Clinical Trial Registry (ChiCTR200034878). Results:A noticeable shift was observed in the gut, oral, and ocular surface microbiota pre-and post-Cana treatment. The post-Cana treatment gut microbiota was more similar to that of the healthy controls. Network correlation analysis revealed that modifications in the gut, oral, and ocular surface microbiota were related to changes in clinical parameters, especially for the ocular surface microbiota. Clinical parameters: A significant decrease in fasting plasma glucose (8.22±2.19vs6.87±1.09mmol/L), glycated serum protein [291.00(264.00,353.00)vs275.00(251.00,342.50) μmol/L], hemoglobin A1c (7.39±1.18vs7.12±1.33%), body mass index (25.32±2.99vs24.83±2.95kg/m2), systolic blood pressure (129.05±17.51vs123.43±14.82mmHg), and urinary creatinine [158.40(74.75,219.15)vs79.70(56.25,138.10) μmmol/kg] levels was noted after 30-day Cana monotherapy (P<0.05). Gut microbiome: Treatment with Cana resulted in an increase in the relative abundance of short-chain fatty acid (SCFA)-producing bacteria, particularly Lachnospiraceae UCG 004, Bacteroides, and Lachnospiraceae NK4A136 group. Oral microbiota: After Cana treatment, a significant increase of Prevotella and Veillonella, both of which are known to be closely associated with SCFAs, was observed. Ocular surface microbiota: Post-Cana administration, the ocular surface microbiota exhibited the most distinct changes in structure and composition. Remarkably, the majority of the increased ocular surface microbiota could produce SCFAs within the gut microbiota. Conclusions:Cana effectively improved the dysregulated glucose metabolism in patients with T2DM. This improvement can potentially be attributed to the restoration of balance among the gut, oral, and ocular surface microbial communities.